Impact of Media on Youth in Pakistan (Global Journal of Management and Business Research, 2013)
Our study is about impact of media on youth in Pakistan. Media has a great impact on one's life. News channel provide the viewers an image of our country where it stands. It can lead a person towards right direction and can also lead a person towards wrong direction as well. It can give us more opportunities as well. It has direct impact on our paradigms. Media creates more complications in relations. It tells us about the current trends and fashions and also helps us in personal grooming. Our youth become liberal due to adaptation of fashion. Last but not the least we discussed music, which creates new pathways in the brain. It gives the peace of mind, relaxation and escapism. Media is a strong power and can b beneficial as well as harmful. We have collected information related to our study from different means and had drawn a conclusion.
Keywords: current trends and fashions; peace of mind; relaxation and escapism